2008
DOI: 10.1017/s0047404508080986
|View full text |Cite
|
Sign up to set email alerts
|

Small talk, high stakes: Interactional disattentiveness in the context of prosocial doctor-patient interaction

Abstract: The literature on “small talk” has not described the way in which this talk, even as it “oils the social wheels of work talk” (Holmes 2000), enables disattending to the instrumental tasks in which one or both participants may be engaged. Small talk in simultaneity can disattend to the movements, bodily invasions, and recording activities functional for the instrumental tasks of medicine. Small talk in sequence occurs in sensitive sequential environments. Surgeons may use small talk to focus away from psychosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 22 publications
0
34
0
1
Order By: Relevance
“…For example, patients may answer 'more than the question' during comprehensive history-taking, 36 make inexplicit requests for a diagnostic test, 37,38 self-initiate problem presentations during prenatal check-ups 39 and resist a doctor's diagnosis 23,40 or treatment recommendation. [41][42][43] In addition, as we discussed in the previous section, there is a handful of studies that have demonstrated how the turn designs selected by doctors can be more or less conducive to subsequent patient participation. 9,[22][23][24] However, CA studies of decision-making in clinical practice have rarely investigated the ways in which doctors might actively invite patients to participate.…”
Section: Models Versus Practices: Our Methodological Starting Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, patients may answer 'more than the question' during comprehensive history-taking, 36 make inexplicit requests for a diagnostic test, 37,38 self-initiate problem presentations during prenatal check-ups 39 and resist a doctor's diagnosis 23,40 or treatment recommendation. [41][42][43] In addition, as we discussed in the previous section, there is a handful of studies that have demonstrated how the turn designs selected by doctors can be more or less conducive to subsequent patient participation. 9,[22][23][24] However, CA studies of decision-making in clinical practice have rarely investigated the ways in which doctors might actively invite patients to participate.…”
Section: Models Versus Practices: Our Methodological Starting Pointmentioning
confidence: 99%
“…For instance, a study in Finnish primary care 41 showed that -even when doctors produce a recommendation in a manner that appears to expect no responsepatients sometimes go on to introduce their own views in ways that succeed in initiating negotiation and subsequent shaping of the final decision delivery by the doctor. Maynard and Hudak 42 have shown how orthopaedic surgeons (in the USA) pursue acceptance of their recommendations and, like Stivers' 45 paediatricians, do not always succeed. By introducing small talk, patients can produce a topic shift away from the recommendation-relevant talk, avoiding the sought-after acceptance.…”
Section: This Focus Began With Stivers'mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on gaze, body movement, spatial alignments and medical instrumentation has elaborated CA into a multi-modal approach and has extended its reach into fields such as surgery (Mondada 2011), anesthesiology (Hindmarsh and Pilnick 2007), dentistry (Hindmarsh et al 2011), and the uses of imaging technologies (Nishizaka 2013). CA methods have also been applied to medical specialties such as cancer (Beach and Anderson 2003), autoimmune deficiency syndrome (Peräkylä and Bor 1990), orthopedics (Hudak and Maynard 2011; Maynard and Hudak 2008), pediatric pain management (Clemente 2009), and a variety of aspects of childbirth (Kitzinger 2011). CA has also been used in studies of sensitive medical care topics such as future illness progression and end of life (Parry et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, all the NESs successfully employed small talk to achieve a number of relational and medical goals (see Coupland, Robinson, & Coupland, 1994;Maynard & Hudak, 2008), although Nina, who was less experienced than the others, made only one social statement. Casual small talk help to give medical encounters a more relaxed conversational tone (Ragan, 2000), and comments about Aaron's parents, for example, aided participants in determining the social circumstance of the patient.…”
Section: Faramentioning
confidence: 99%